A ausência de uma política extrafiscal para o desenvolvimento de biotecnologia aplicada a processos de biorremediação marinha de petroderivados - Araújo, Ricardo da Silva (2023)
The various oil activities developed along the Brazilian coast have the potential to cause harmful impacts on the environment. Therefore, one way to reverse its harmful effects is through the degradation of its byproducts through the use of biotechnology in remediation processes. In this sense, as one of the ways of protecting the ecological balance, the Brazilian State, in its Power to Tax, has the objective of supplying resources to the public coffers and providing the common good to the people, with the possibility of extra-fiscal incentives capable of promoting environmentally appropriate actions and practices. In this way, the Executive and Legislative powers can, through extra-fiscality, guarantee the development of new biotechnologies for the remediation of petroderivatives, in addition to adapting the National Contingency Plan to the use of bioremediation techniques for these compounds. Thus, the present work aimed to analyze the current fiscal policies adopted for the development of petroleum activity, comparing them to the extra-fiscal incentives given to the biotechnological production of bioremediation processes of petroleum derivatives from the Brazilian marine coast. And, focusing on this issue, the present work was divided into three chapters, which brought the theoretical discussion related to extra-fiscality as a tax policy for environmental preservation. It also demonstrated the main characteristics of the petroderivatives of interest for this study and the main biotechnological processes for removing petroderivatives in the marine environment and, in the end, discussed extrafiscal policies in the development and use of biotechnology techniques to be applied in preserving the environment. environment, highlighting as a result the lack of a specific extra-fiscal instrument aimed exclusively at biotechnological development for the bioremediation of petroderivatives on the Brazilian coast. To this end, the methodology used was a bibliographical review and a free exploratory approach to the topic, in which extra-fiscality and tax incentives, petroderivatives and